PERANCANGAN ALAT PENYARINGAN DALAM PROSES PEMBUATAN TAHU - Mulyana, Ig. Jaka; Santosa, L.M. Hadi; Prasetya, Wahyu (Jurnal Ilmiah Teknik Industri, 2013)
CV. Segitiga is a company engaged in tofu manufacture. In the manual screening process, workers perform screening activities with standing postures and the hands shaking sieve so that workers spend a lot of energy that causes a long time as well as the screening process less efficient. Besides, the use of a manual screening causes pain complaints of workers in some parts of the workersâ body. In this study, a screening tool designed to facilitate the work and shorten the time of screening in the process of making tofu. Tools that have been created using the motor so can reduce worker fatigue and injury and speed up screening process. By using the tool, the savings are Rp. 1.000.600/month and screening times can be shortened by 55.1%.